Developing a Social Entrepreneurship-Based Nonformal Education Curriculum for the Socioeconomic Reintegration of Divorced Former Migrant Women in Indonesia - Rofik Rosyanafi; Gunarti Dwi Lestari; Wiwin Yulianingsih; Rivo Nugroho (MASI Mandiri Edukasi, 2026)
This study aimed to develop and validate a nonformal education curriculum for socioeconomic reintegration of divorced former migrant women in Ponorogo, Indonesia. A Design and Development Research approach was applied through three phases: needs analysis (n = 20), curriculum design and development, and expert validation, followed by a limited try-out (n = 12). Data were collected through interviews, focus group discussions, document analysis, competency gap assessment, expert judgment, and field observation. Expert validation showed high feasibility with mean scores for content relevance (M = 4.60), learning outcomes (M = 4.50), gender responsiveness (M = 4.40), and feasibility (M = 4.20). The try-out demonstrated strong implementation outcomes, including participant comprehension (M = 4.25), participation consistency (M = 4.30), and satisfaction (M = 4.35). Findings indicate that economic reintegration and social entrepreneurship competencies are the primary learning needs, with psychosocial strengthening and digital literacy as supporting areas. The study concludes that the developed curriculum is valid, feasible, and practical, and suggests that nonformal education policy should adopt integrated reintegration-oriented curriculum models for vulnerable adult groups.